Counseling on Early Stunting Prevention Efforts with Riau University KKN Students in Munsalo Kopah Village - Erda, Gustriza; Siregar, Nurainun; Ramadhani, Fitri; Efendi, MHD; Mistika, Lensi; Ferdinan, Tri Agus; Jannah, Miftahul; Anisa, Rahmatul; Putri, Nelsa; Mariza; Al Baihaqi, Habib (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
Stunting is a condition of chronic malnutrition that can cause children to experience health problems such as susceptibility to disease and a decrease in productivity levels. Factors that can cause stunting include insufficient food sources, parenting, and economic conditions. This work program aims to increase public knowledge about stunting in children from an early age. As well as educating parents about foods that can prevent stunting in children. Socialization is carried out in the form of delivering material related to counseling on what stunting is, its characteristics, the impact of stunting, and prevention of stunting. The low knowledge of mothers about stunting in Munsaloh Village encouraged Riau University KKN students to invite the community to participate in counseling efforts to prevent stunting from an early age. Understanding about stunting counseling efforts is expected to help the community increase knowledge about fulfilling balanced nutrition, exclusive breastfeeding, and complementary foods (MPASI) as a form of prevention against stunting.